TINJAUAN HUKUM FIKIH TERHADAP HADIAH TABUNGAN DAN GIRO DARI BANK SYARI'AH - Hosen, Muhammad Nadratuzzaman; Muayyad, Deden Misbahudin (ALQALAM, 2013)
This article explains about the Islamic law of gift from Bank to customers related to saving and gyro accounts of Islamic Bank. The Islamic Banks give gift directly  and  indirectly  to  new  ettstomers  and  old  customers  through drawing  (qur'ah) or lottery and non-drawing. There are disputes (ikhtilaf) among Islamic Law  Experts (Fuqaha’) about the status of law when Islamic Banks give the gift. Hanafi and  Syafi'i  Schools  of thought  opined  that  the gift  can  be given  to  the customers as long as there is no agreement between bank and costomers meanwhile the banks still have a debt to consumers, this is permissible. Maliki and Hanbali schools opined that the gift is not permissible during the time of borrowing and lending. Majority Islamic Exsperts allow to give gift after banks have already paid back the debt to consumers as long as there is no agreement between bank and cusiomers, but Maliki School do not allow lo give gift at that condition. Also, for giving gift should free from gambling or elements of gambling (muqamarah).  The method of this article is using literature reviews from classical Islamic Law's books and contemporary Islamic law's books related to drawing or lottery and gambling, meanwhile the aims if this mticle are to investigate the law status if gift from bank to new customers and old customers with direct and indirect ways.   Keywords : gift, saving and gyro accounts, disputes, drawing and elements of gambling